Saroglitazar for the treatment of hypertrig-lyceridemia in patients with type 2 diabetes: current evidence - Sosale, Aravind (Diabetes Metab Syndr Obes, 2015)
Diabetes mellitus (DM) is one of the most dreaded metabolic disorders in the world today. It is the leading cause of morbidity and mortality, and plays a cardinal role in quality of life and health economics. DM is associated with a high prevalence of microvascular and macrovascular complications. DM is a very important cardiovascular (CV) risk factor. Cardiovascular disease (CVD) has been implicated as the prime cause of mortality and morbidity in patients with DM. Hence, treatment of DM goes beyond glycemic control, and demands a multidisciplinary approach that comprehensively targets risk factors inherent in CV events. Lipid abnormalities are undoubtedly common in patients with DM, and they contribute to an increased risk of CVD. A high-risk lipid profile, termed atherogenic dyslipidemia of diabetes (ADD), is known to occur in patients with DM. The use of lipid-lowering agents, a quintessential part of the multifactorial risk factor approach, is a crucial intervention to minimize diabetes-related complications. In this article, we discuss the role of peroxisome proliferator activator receptor (PPAR) alpha/gamma (α/γ) agonist, saroglitazar, in the management of ADD. While statins are irrefutably the first line of drugs for dyslipidemia management in patients with residual CV risk while on a statin, PPAR α/γ agonists have been found to be of substantial benefit. Data from the PRESS I–VI clinical trials testify to the fact that saroglitazar and fibrates have similar efficacy in reducing triglycerides and improving high-density lipoprotein. The ancillary benefit of improved glycemic control, without the weight gain of PPAR γ agonists, is an added advantage. Reduction in ADD, improved glycemic control, efficacy at par with fibrates, and an acceptable safety profile form the grounds on which this group of PPAR α/γ agonists, with their novel mechanism, holds a promising future in the management of diabetic dyslipidemia.